Analisis Pendekatan Saintifik pada Buku Siswa Kelas 4 SD Tema 7 “Indahnya Keragaman Negeriku” Revisi Tahun 2017 - Rohmat, Rianda Asrul (FKIP Unirow Tuban, 2022)
This research was conducted to see the consistency of scientific approaches in the book of 4th grade students of Elementary School Theme 7 Beautiful Diversity in My Country revised 2017. The purpose of this study is because in the initial analysis in learning 5 sub-themes 1 found that there is no scientific component of raising and communicating. The method used in this research is descriptive method with a qualitative approach. Sample the data used throughout the learning in each sub theme. Data collection is carried out using instruments guided by Permendikbud number 22 of 2016 which contains 5 components of a cyantifik approach to observing, increasing collecting information, reasoning, and communicating. The stages of data analysis include data reduction, data presentation, and conclusion drawing.based on the results of research conducted it was found that the scientific approach is quite complete but there is a scientific approach that is not complete.For the most scientific approach is the skill of observing. Every learning contained in every sub theme already exists. For a slightly pailing scientific approach, it is the ability to communicate. For this reason, there needs to be a revision for the Class IV Student Book Theme 7 Beautiful diversity in My Country.